2005
DOI: 10.1109/titb.2004.840067
|View full text |Cite
|
Sign up to set email alerts
|

Airmed-cardio: a GSM and Internet services-based system for out-of-hospital follow-up of cardiac patients

Abstract: A platform built around three information entities (patient, health-care_agent, and central_station) was designed to enable patients with chronic heart disease (in stable condition; emergency situations were excluded deliberately) to complete specifically defined protocols for out-of-hospital follow-up and monitoring. The patients belonged to one of four specific risk groups: arterial hypertension, malignant arrhythmias, heart failure, and postinfarction rehabilitation. They were provided with portable recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 26 publications
0
50
0
4
Order By: Relevance
“…While government-led telehealth initiatives tend to focus on video conferencing, a number of small studies and pilot projects delivering health services via the Internet have been reported in patients with breast cancer (21,22), asthma (23), chronic obstructive pulmonary disease (24,25), diabetes (26)(27)(28)(29)(30)(31)(32), lung transplantation (33), overweight (34)(35)(36)(37)(38)(39)(40), smokers (41), chronic heart failure (25,(42)(43)(44) and CVD (45)(46)(47)(48). These studies demonstrated that patients were willing to enter self-measured data online and communicate with health care providers via e-mail and/or chat/video conferencing.…”
Section: Discussionmentioning
confidence: 99%
“…While government-led telehealth initiatives tend to focus on video conferencing, a number of small studies and pilot projects delivering health services via the Internet have been reported in patients with breast cancer (21,22), asthma (23), chronic obstructive pulmonary disease (24,25), diabetes (26)(27)(28)(29)(30)(31)(32), lung transplantation (33), overweight (34)(35)(36)(37)(38)(39)(40), smokers (41), chronic heart failure (25,(42)(43)(44) and CVD (45)(46)(47)(48). These studies demonstrated that patients were willing to enter self-measured data online and communicate with health care providers via e-mail and/or chat/video conferencing.…”
Section: Discussionmentioning
confidence: 99%
“…The same platform could be applied to SH in healthcare. Airmed-cardio [100] is an MTS based monitoring system for cardiac patients follow-up in their home. Each patient has a portable monitoring equipment and cellular phone that supports data transmission.…”
Section: Mobile Telecommunications System (Mts)mentioning
confidence: 99%
“…Como soporte tecnológico de los proyectos piloto y ensayos clínicos ha sido diseña-da, puesta en funcionamiento y mantenida por un equipo de tres ingenieros, una plataforma denominada Airmed 18 , la cual se compone de cinco componentes (figura 3), cuyos principales requerimientos funcionales son:…”
Section: Plataforma Airmedunclassified